Phanera larseniana (Leguminosae: Cercidoideae), a new species from Thailand - Chantaranothai, Pranom; Mattapha, Sawai; Wangwasit, Khanit (Phytotaxa, 2017)
Phanera larseniana, a new species from north–eastern Thailand, is described and illustrated. It most closely resembles P. rubro-villosa but differs in the length of the floral parts, and in the number and position of the staminodes. The species is known only from a single locality in north-eastern Thailand. An illustration and photos of the new species are provided.